2008
DOI: 10.4141/cjps07087
|View full text |Cite
|
Sign up to set email alerts
|

Performance of prohexadione-calcium on shoot growth and fruit quality of apple — Effect of spray surfactants

Abstract: . 2008. Performance of prohexadione-calcium on shoot growth and fruit quality of apple * Effect of spray surfactants. Can. J. Plant Sci. 88: 165Á174. Vegetative growth control of apples (Malus )domestica Borkh.) is necessary to maintain a balance between growth and cropping. Pruning is a labour-intensive management practice to achieve this and intrinsically stimulates new growth. Prohexadione-calcium (PC) is a plant bioregulator that effectively regulates the shoot extension growth of apples and other tree fru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
20
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 17 publications
5
20
0
4
Order By: Relevance
“…However, Pro-Ca, a GA inhibitor, had no evident effect on flowering, yield and alternate bearing in our study. Similar observations were also found by Cline et al (2008) and Duyvelshoff and Cline (2013). Byers et al (2004) reported that the effect of Pro-Ca on flowering is neutral.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…However, Pro-Ca, a GA inhibitor, had no evident effect on flowering, yield and alternate bearing in our study. Similar observations were also found by Cline et al (2008) and Duyvelshoff and Cline (2013). Byers et al (2004) reported that the effect of Pro-Ca on flowering is neutral.…”
Section: Discussionsupporting
confidence: 77%
“…Treatment with Pro-Ca reduced shoot length by 21-71% in apples depending on the dose, timing of treatment and cultivar (Miller 2002). Similar effects were observed in 'Smoothee Golden Delicious' (Medjdoub et al 2004), 'Empire' (Cline et al 2008), and'Royal Gala' and'Fuji' (Mata et al 2006) apple trees. These reports accord with our findings showing that Pro-Ca inhibits the lengthening of apple shoots.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…En frutales templados caducifolios, P-Ca se ha aplicado en dosis de 50 a 250 mg L -1 simples o repetidas durante y después de floración (2 y 4 aplicaciones, a intervalos de 14-20 días) con resultados positivos en reducción de la longitud del brote (18-50%) Ramírez et al, 2006;Cline et al, 2008;Kiessling-Davison et al, 2008;Einhorn et al, 2014), incremento en amarre y producción de fruto (21-63, 22%, respectivamente) en manzano 'Golden Delicious/MM106' (Ramírez et al, 2006) y producción en pera 'William' y manzano 'Fuji', 50-40 %, respectivamente . Aunque en pera 'Blanquilla' (Asin et al, 2007) y 'D'Anjou' (Einhorn et al, 2014) no se encontró efecto en intensidad de floración y rendimiento.…”
Section: Introductionunclassified
“…Sob tais condições, o uso de técni-cas de manejo que restrinjam o desenvolvimento vegetativo torna-se imprescindível. O controle do desenvolvimento vegetativo da macieira pela poda verde e pela poda hibernal é essencial para garantir a produtividade do pomar e otimizar a qualidade dos frutos (CLINE et al, 2008). No entanto, a poda é uma das práticas de manejo mais dispendiosas em tempo e em mão de obra na produção de maçãs, especialmente quando as plantas são vigorosas (PRIVÉ et al, 2006).…”
Section: Introductionunclassified